KOMUNIKASI POLITIK PADA PEMILIHAN UMUM 2014 - Atmadji Sumarkidjo (Jurnal Visi Komunikasi, 2014)
Jokowi name in early 2013 emerged as a candidate for the "newest" Presiden RI 2014dramatically changed the political map in Indonesia. From March 2013 until January 2014 thename of Joko Widodo has always topped the surveys or polls were held, despite the PDI-Struggle(PDI-P), which is the bearer party official Jokowi until early February 2014 was never officiallyannounced their names as candidates of their President in Presidential Election come.This is known as Jokowi Effect. Has five characteristics of, first, the emergence of the name ofthe former mayor of Solo, who only three months in office as Governor of Jakarta to exchange aPresidential candidate in the 2014 polls. Second, the bandwagon effect after Jokowi nameappeared in the survey on social media and then knowingly disseminated through conventionalmass media such as newspapers and television.Third, the emergence of Jokowi name with thepopularity and the highest elektabilitas consistently in surveys throughout the year 2013 haschanged the landscape of national political calculations competition 2014 candidates.Pemilihan Umum (Pemilu) sudah didepan mata. Pemilihan untuk menentukananggota-anggota DPR-RI, DPRD I dan DPRD II akan diselenggarakan pada 9 April 2014sementara pemilihan Presiden akan dilaksanakan pada 9 Juli 2014. Tidak mengherankan paracalon legislatif sudah bersiap untuk dikenal, diketahui dan nantinya dipilih oleh parakonstituennya, dan meskipun periode untuk kampanye secara resmi dimulai 11 Januari 2014.Nama Jokowi pada awal tahun 2013 muncul sebagai kandidat “terbaru” Pres iden RI 2014mengubah secara dramatis peta politik di Indonesia. Sejak Maret 2013 hingga Januari 2014 namaJoko Widodo selalu menduduki peringkat teratas berbagai survei atau poll yang diselenggarakan,meskipun PDI-Perjuangan (PDIP) yang merupakan partai pengusung resmi Jokowi sampai awalFebruari 2014 tidak pernah secara resmi mengumumkan namanya sebagai bakal calon Presidenmereka pada Pilpres mendatang.